DINÂMICA POPULACIONAL, PERÍODO REPRODUTIVO E SENSILAS ANTENAIS DE EUETHEOLA HUMILIS (COLEOPTERA, SCARABAEIDAE, DYNASTINAE) - CONCEIÇÃO, Jessé Santarém; RODRIGUES, Sergio Roberto (ANAIS DO ENIC, 2024)
-